Representasi Kecantikan Perempuan Indonesia Dalam Media Sosial Instagram @Projectpuanid - Anggi Yus Susilowati; Rani Ika Wijayanti (Department of Sociology Faculty of Social and Political Sciences, 2022)
This study aims to determine the representation of Indonesian female’s beauty in Project Puan. This study uses a qualitative approach with purposive sampling as observation data collection techniques on the @projectpuanid’s Instagram account. The analytical method that used is Roland Barthes' semiotic theory. The results of the study show that this account represents women’s beauty differently as usually shown in media. Female’s beauty according to this account is hers who have diversity in physical form due to different racial factors.